THE ROLE OF EUROPEAN BANK FOR RECONSTRUCTION AND DEVELOPMENT IN PROMOTING ENVIRONMENTALLY SOUND AND SUSTAINABLE DEVELOPMENT - CONSTANTIN BRĂGARU (Challenges of the Knowledge Society)
One of the most important development banks which finances private initiatives in the Central and Eastern Europe countries is the European Bank for Reconstruction and Development (EBRD). EBRD as international financial institution plays a very important role in the development of many sectors such as agribusiness, energy efficiency, financial institutions, manufacturing, municipal and environmental infrastructure, natural resources, power and energy, property and tourism, telecommunications, information technology and media, transport. Its objectives aim to promote transition to market economies by investing mainly in the private sector, to mobilize significant foreign direct investment, to support privatization, restructuring and better municipal services to improve people’s lives and to encourage environmentally sound and sustainable development. The present scientific article focuses on the last objective respectively the bank commitment to promote environmentally sound and sustainable development and shortly presents EBRD environmental policy because EBRD, unlike other development banks, has strong and imperative regulations regarding this issue. This is why all the EBRD potential beneficiaries must prove that their projects are environmentally sound.